Potential environment and socio-economic impact of biofuel production in Malaysia: A preliminary review - Mohan D.; Essam Y.; Katman H.Y.B.; Ahmed A.N.; Shamsuddin A.H. (IOP Publishing Ltd, 2023)
Biofuels; Deforestation; Disasters; Economic and social effects; Effluents; Gas emissions; Greenhouse effect; Greenhouse gases; Industrial economics; Land use; Petroleum industry; Water pollution; Biofuel production; Land-use change; Oil industries; Oil producers; On potentials; Palm oil mill effluents; Socio-economic impacts; Socio-economics; Palm oil